Transformation of Women Politicians in Parliament - Evi Muafiah (AL-TAHRIR, 2019)
Abstract: Women’s representation in politics in Indonesia has been secured despite inequal percentage compared to the men. For instance, the results of the 2019 legislative elections for women only accounted for 20.5% or 118 seats of the 560 existing seats. On the other hand, it seems that the performance of women in parliament is also questionable. Thus, this research was conducted to find out and understand how was the performance of women politicians, their contribution to women empowerment and the obstacles they faced. This descriptive-explorative qualitative research was conducted in Ponorogo as a district in the former Residency of Madiun which always gets the highest number of women politicians in each elections until 2019. The research subjects were selected using purposive sampling toward women legislature members of DPRD Ponorogo. Meanwhile, the data was obtained through interviews, observation, and documentation. Furthermore, for the data analysis the author employed Harvard gender analysis and used data triangulation as one of the data verification techniques. The results of this study concluded that the performance of women legislative members was less satisfactory. This can be seen from 3 aspects; responsiveness, accountability and effectiveness. In addition, some obstacles they faced are (a) the strong patriarchal culture in the legislative environment, (b) weak coordination among women legislative members, (c) patterns of relationships that are built on a transactional basis, and (d) politically charged programs.